Kepatuhan Minum Antibiotik Pasien Rawat Jalan di Klinik Yonkes 2/2 Kostrad Malang - Rudy Mardianto; Nanang Ardianto; Pujianto Pujianto (Jurnal Kesehatan Hesti Wira Sakti, 2021)
ABSTRACT Introduction: Bacterial resistance to antibiotics is such a serious problem that it must be handled appropriately. Adherence to taking antibiotics is an effort to prevent resistance. Antibiotics as anti-infectives are given in one cycle of therapy so they must be taken to the end to prevent resistance. This study aims to find out the compliance of taking antibiotics in outpatients at Yonkes 2/2 Kostrad Malang clinic. Methode: The research design is observational with a cross sectional study approach. The sampling techniques is purposive sampling and obtained 100 patients who meet the criteria of inclusion and exclusion. The study was conducted using questionnaires as well as drug use forms. Results: The results showed that the characteristic antibiotics used amoxycilin 79%, cefadroxyl 12% and metronidazole 9%. The length of antibiotic use of 3 days as much as 76% and 5 days as much as 24%. The results of measurements with questionnaires showed that the categories were good at 47%, the categories were quite 18% and the categories were less than 35%. Pill count methods showed that compliance was 49% and non-compliant 51%. Conclusion: The level of adherence to taking antibiotics with questionnaires and pill counts methods show relatively similar results. Keywords: Compliance, questionnaires, pill count